PERAN MANAJEMEN REKRUTMEN TENAGA PENDIDIK DALAM MENINGKATKAN MUTU PENDIDIKAN SEKOLAH MENEGAH - Miftahul Huda (JURNAL PENDIDIKAN DAN KEGURUAN, 2024)
The aim of this research is to find out how the implementation of teaching staff recruitment management can improve the quality of education at SMP NU Al Islami. The methods used include conducting needs analysis, position analysis, determining the right candidate, choosing the most appropriate method, calling candidates who are deemed to meet the job requirements, selecting new teacher candidates, placing new educators, results, and supporting and inhibiting factors. This study uses qualitative and descriptive methodology. Primary data from main sources and secondary data from other sources were collected. Interviews, observation, and documentation are the methods used to collect data. The research results show that the implementation of teacher recruitment management to improve the quality of education at SMP NU Al Islami is simple and friendly. One of the results achieved is a needs analysis, which evaluates the condition of the school environment and the current availability of positions. Job analysis, which determines the general requirements of prospective educators to fill needed positions, such as a bachelor's degree. Because every step has been carried out in the teaching staff recruitment management process, the results are said to be good.